Fusion motion capture: accuracy of motion capture without cameras for alpine ski racing - Brodle, M.; Walmsley, A.; Page, W. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: Selected aspects of the design and validity testing of the Fusion Motion Capture System for alpine ski racing are the topics of this paper. Fusion Motion Capture is a wearable motion capture System utilizing GPS and inertial measurement units (IMUs) developed by the author. Other Instruments can also be included such as force platforms, pressure sensitive insoles, and cameras. Fusion Motion Capture may provide valuable information to sports such as alpine ski racing, where the motion of interest covers a large volume because it allows the whole performance to be captured automatically. Several papers incorporating IMUs were presented at the recent ISB Conference. The wide range of accuracy reported from IMU measurements suggests that that the accuracy of the sensors may be dependant on the particular application. An IMU contains accelerometers, gyroscopes, and magnetometers. They can provide estimates of 3D orientation, angular velocity, and linear acceleration. If the athlete accelerates through global space fusion motion capture accuracy may be improved by additional information from GPS, camera, timing gates, or some other global measurement.